(untitled) (Scientific journal of the Fergana State University, 2023)
The comparative relation is a concept that has been studied in linguistics; the new view of its study is realized through the analysis of its constructions in modern linguistics. In particular, this article describes the comparative relation in terms of its new elements and semantic types in the example of English and Uzbek languages